A decriptive survey on the preferences of selected female supermarket shoppers on reusable bag attributes - Cueva, Lorraine Mancio (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This is a descriptive study about selected female supermarket shoppers and their preferred design and functional features of a reusable bag. It sought to determine their preferences on reusable bag attributes. The study also determined if these women use the bag frequently and consistently and for which purpose they use the bag. The many variations the reusable bag has taken into form provide an opportunity to understand consumer preferences, so that designers and businesses may utilize these design elements that will encourage frequent and consistent use of the bag, as well advertisement. Using purposive sampling, fifty-five women who have used or continue to use reusable bags for grocery shopping were asked to participate in a survey. A questionnaire was distributed among the respondents to obtain information on the following: 1) consistency of usage of the reusable bag; 2) purposes of using the bag; 3) the preferred reusable bag features of the respondents; and 4) level of agreement of the respondents toward some situations concerning some features of the reusable bag. The Likert Scale was applied as one of the tools of measurement for the study. Results were tallied and their frequencies were taken. Some comments from the respondents were also given to explain some of their choices. The numerical data were illustrated using bar graphs and pie charts. The results from the survey revealed that 33% and 35% of the shoppers use their reusable bags for shopping groceries indicated by their answers of only ?sometimes? and ?often?, and with forgetfulness being the common reason for not using the bag all the time. Plastic bags during the point of purchase were still used as these can be reused or to separate purchases such as detergents from food. The study found that they frequently but inconsistently use the reusable bag. For most of them, the reusable bag is utilized for all their purchases and other dry goods such as packaged food. A medium-size bag was preferred by most of the respondents. The natural-fiber canvas was the leading choice of material, and the tote-style bag was the preferred construction. Aside from the bag?s size, other preferred features include foldability, durability in material and construction, and washability. Designers can use these findings to create a bag that will suit the needs of the supermarket shopper, as well as take the advantage for businesses to use the bag as a mobile advertisement. Encouraging the use of the bag with frequency and consistency may also help address the global issue of plastic bag pollution.